HIV risk perception and behavior among sex workers in three major urban centers of Mozambique. - Judite Langa; César Sousa; Mohsin Sidat; Karen Kroeger; Eleanor McLellan-Lemal; Hrishikesh Belani; Shama Patel; Daniel Shodell; Michael Shodell; Irene Benech; Richard Needle (PLoS ONE, 2014)
HIV risk perceptions and behaviors of 236 commercial sex workers from three major Mozambican urban centers were studied using the International Rapid Assessment, Response and Evaluation (I-RARE) methodology. All were offered HIV testing and, in Maputo, syphilis testing was offered as well. Sixty-three of the 236 opted for HIV testing, with 30 (48%) testing positive for HIV. In Maputo, all 30 receiving HIV tests also had syphilis testing, with 6 (20%) found to be positive. Results include interview excerpts and qualitative results using I-RARE methodology and AnSWR-assisted analyses of the interviews and focus group sessions.